Audit committee role, firm size, financial distress, and audit quality on financial reporting integrity: an Islamic ethical perspective - Maida Nurdianti; Faqiatul Mariya Waharini (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2025)
This study examines the influence of the audit committee, firm size, and financial distress on the integrity of financial reporting, with audit quality as a moderating variable in state-owned enterprises listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Using a quantitative approach, data were collected from the annual reports of 20 companies, yielding 80 firm-year observations. Financial reporting integrity reflects honesty and accuracy in presenting a company’s financial condition. The findings show that the audit committee has a significant positive effect, firm size has a significant negative effect, and financial distress has no significant effect on financial reporting integrity. The Moderated Regression Analysis (MRA) indicates that audit quality moderates the relationship between the audit committee and firm size on reporting integrity but does not moderate the effect of financial distress. These results highlight the vital role of the audit committee and firm size in enhancing the integrity of financial reports, while audit quality serves as a strengthening factor. The study contributes to improving corporate governance practices by emphasizing that integrity in financial reporting is not only a technical issue but also a moral obligation grounded in Islamic ethical values of truthfulness, trustworthiness, and justice.